História de Capela : o uso da história local nos anos finais do ensino fundamental - Costa, Edijan Santos (2021)
This work approaches the main characteristics of local history and the possibilities of its use in the classroom; the research is about the history of Capela town, in the state of Sergipe, from the emergence of the village that would give rise to town in the first half of the 18th century. Dealing with themes as the importance of sugar cane to Capela's economy, the culture in the country, by the history of the traditional Festa do Mastro, the importance of environmental preservation with the Mata do Junco Wildlife Refuge, the fight for access to land in the Santa Clara settlement, the quilombola communities, the passages of Lampião’s gang by Capela and the participation of a Capelian nurse in the Second World War. The final product resulting from this work is a booklet on various aspects of the history of Capela, prepared with the aim of subsidizing the work of History teachers who work in the city, as well as enabling give students access to the history of the place they live through educational material from easy to understand. The idea of carrying out this work came after the realization that the most students in the final years of elementary school at the State School Professor Maria Berenice Barreto Alves, located in Capela, where I teach the discipline of History, ignore important aspects of the history of the place. This school, as well as the other state schools located in town, doesn´t have teaching material on local history that could facilitate the teachers' work, and then I consider the development this work very relevant.